Development of a Project-Based Comprehensive Assessment Tool Model for Integrated Mathematics Learning in Elementary School Curriculum in Wetland Environments - Darmiyati, Darmiyati; Novitawati, Novitawati (PT. Riset Press International, 2024)
The aim of this research is to determine the initial conditions, analyze, produce elementary school mathematics learning tools based on project assessment in a wetland environment that are valid and reliable and to determine the effectiveness of primary school mathematics learning tools based on project assessment in a wetland environment simultaneously. The type of R&D research used in this research is the Borg and Gall design model with pre-field, field survey and post-field stages. The results of the assessment of project-based instruments from experts and practitioners in carrying out internal tests received good marks. The project-based comprehensiveness assessment instrument that has been formulated and tested by researchers can be said to have high validity, namely exceeding ≥0.40. The conclusion in this research is that the development of a project-based comprehensive assessment tool model through mathematics learning activities helps teachers provide direct assessments, identify learning objectives, see student progress over time, and describe students' mastery of the material, especially in mathematics learning